PERFORMANCE ANALYSIS OF JALAN PIET A. TALLO IN KUPANG CITY - Ivana Annabella Adam; Christina Sari; Budi Hartanto Susilo; Dewi Rintawati (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2023)
Jalan Piet A. Tallo is a major arterial road connecting several areas with the city center of Kupang. The large traffic flow that passes through Jalan Piet A. Tallo, resulting in traffic congestion during rush hour, is the background of this research. This research aims to determine the right alternative solution to reduce traffic congestion on Jalan Piet A. Tallo. This research uses a descriptive method by obtaining data directly from surveys and analyzing the data according to the guidelines of the 1997 Indonesian Road Capacity Manual (MKJI). Then, the analysis produces values for the degree of saturation (DS) and level of service (LOS) of the road. Overall, from the results of this research, traffic jams are caused by several factors; namely, there is a narrowing of the road from road type 4/2 D to type 2/2 UD, many vehicles enter and exit from Jalan M. Sabaat to Jalan Piet A. Tallo, and many drivers still violate traffic signs. Therefore, an alternative that can be done is to contact the relevant authorities about the prohibition of right turns onto Jalan M. Sabaat and the need to install road dividers from STA 0+300 to STA 0+550. Apart from this, the road can be widened by 1.7 m in the inner city lanes so that the degree of saturation (DS) during the afternoon rush hour can be reduced by 12.67% to 0.875. Another alternative is to change the road geometry from type 2/2 UD to 4/2 D and build a new connecting bridge. Thus, the degree of saturation (DS) during the afternoon rush hour decreases by 52.89% to 0.472. This value shows that the traffic flow is stable and the speed is controlled. Keywords: Road Performance, Congestion, Piet A. Tallo Road, Kupang City